2022
DOI: 10.3390/antiox11102066
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotics from Oregano Extracts Enhance the Intestinal Health and Growth Performance of Pigs

Abstract: This study aimed to investigate the effects of phytobiotics on the intestinal health and growth performance of pigs. Totals of 40 newly-weaned pigs with 6.4 ± 0.3 kg BW (Exp. 1) and 120 growing pigs with 27.9 ± 2.3 kg BW (Exp. 2) were allotted in RCBD in a 2 × 2 factorial arrangement. The factors were: antibiotics as growth promoter (AGP) and phytobiotics (PHY). Pigs were fed experimental diets during 21 d (Exp. 1) and 42 d (Exp. 2). Growth performance, health parameters, and nutrient digestibility were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Increasing supplemental levels of β-mannanase linearly reduced TNF-α, IgG, MDA, and PC both in the duodenum and the jejunum of nursery pigs. The TNF-α, a pro-inflammatory cytokine, along with IgG, an immunoglobulin, are key mediators of inflammatory response, and MDA and PC are products of oxidative damage ( Duarte and Kim, 2022 ; Deng et al., 2023b ; Jang et al., 2023b ). Previous studies have shown that the decreases in TNF-α and IgG ( Holanda and Kim, 2022 ; Deng et al., 2023a ) and MDA and PC ( Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing supplemental levels of β-mannanase linearly reduced TNF-α, IgG, MDA, and PC both in the duodenum and the jejunum of nursery pigs. The TNF-α, a pro-inflammatory cytokine, along with IgG, an immunoglobulin, are key mediators of inflammatory response, and MDA and PC are products of oxidative damage ( Duarte and Kim, 2022 ; Deng et al., 2023b ; Jang et al., 2023b ). Previous studies have shown that the decreases in TNF-α and IgG ( Holanda and Kim, 2022 ; Deng et al., 2023a ) and MDA and PC ( Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The tight junction proteins were measured as previously reported by Duarte and Kim [ 37 ]. Briefly, the total protein of the duodenum and jejunum were extracted by using RIPA Lysis and Extraction Buffer (content: 25 mmol/L Tris-HCl, pH 7.6, 150 mmol/L NaCl, 1% NP-40, 1% sodium deoxycholate, 0.1% SDS) (89900, Thermo Fisher Scientific Inc.), with the supplementation of Halt Protease Inhibitor Cocktail (100 ×) (87786, Thermo Fisher Scientific Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Organic acids and EO blends work in synergy to suppress growth of pathogenic microbes and promote the growth of beneficial microbes [ 55 ]. Formic acid, fumaric acid, and citric acid reduced the incidence and severity of diarrhea, increased microbial diversity in the GIT, and reduced E. coli counts while increasing lactobacilli counts [ 22 , 56 , 57 ]. Herb and plant extracts reduced the E. coli count and improved energy digestion [ 58 , 59 ].…”
Section: Effect Of Organic Acids and Essential Oils On Pig Performancementioning
confidence: 99%